Anthropometric profile, body composition and somatotyping of national Iranian cross-country runners - Bahman Mırzaeı; Hadi Nobarı; Hamid Arazı (Türk Spor ve Egzersiz Dergisi)
This study was conducted to determine the anthropometric profile of selected national athletes. The purpose of this study was to find out anthropometric measurements, body composition and somatotyping of Iranian cross-country runners. The participants were 9 male national Iranian cross-country runners. The age of athletes was between 20 to 32 years. Cross-country personal best 36min 55s (47s); training volume: 120-180 km.wk; All subjects were assessed for height, weight, breadths, lengths, girths and skin-fold thickness. Percentage of body fat was calculated from the sum of 7 measurements of skin-fold thickness. The somatotype and height to weight ratio (HWR) as well as the skin-folds extremity to trunk ratio (E:T) were also calculated. The Mean (SD) of LBM (Lean Body Mass), %BF (Body Fat), WHR (Waist Hip Ratio), HWR (Height to Weight Ratio), E:T (Extremity/Trunk) skin-fold ratio, SAD (Somatotype Attitudinal Distance) and Manourrier were 60.36 (8.25), 8.07 (1.71) %, .82 (.06), 44.01 (1.00), .77 (.17), 0.90 (0.33) and 1.10 (.63), respectively. The Mean (SD) endomorph, mesomorph and ectomorph were 1.43 (.43), 4.10 (.56), and 3.63 (.73), respectively. National Iranian cross-country runners seem to have mesomorph and ectomorph are equal (or do not differ by more than one-half unit), and endomorph is smaller. Despite population comparisons would be required to identify any connection between specific anthropometric dimensions, these reference data reported in the present study for useful to practitioners and researchers, carry immense practical application and should be useful for future investigation on endurance runners selection, talent identification in cross-country running and training program development.